Urban Quality of Life: A Rubik cube of objective and subjective descriptors - Keul, Alexander G.; Brunner, Bernhard; Blaschke, Thomas (Momentum Quarterly, 2017)
In the field of urban Quality of Life (QOL), objective Geographic Information Science (GIS) data has merged with subjective wellbeing. The scientific discourse shows a diversity of variables, a paucity of organizing theories, and continued efforts to capture the phenomena with mixed methods. An urban QOL project in Salzburg, Austria surveyed 16 city districts via 802 geocoded datasets. Urban stress (e.g. density) and recovery (e.g. green space) were contrasted, and Detroit Area QOL items together with city planning GIS data were used. In a first step, a reliable three-dimensional psychological construct for QOL (Environmental/Social Quality, Social Roots, Subjective Infrastructure) was built. Two factors also had GIS predictors, while Social Roots did not. Significant district differences underlined the importance of sociocultural microsystems. A second step tested whether the psychological descriptors are city-specific or general. Subjective QOL data on Salzburg City were compared with samples from Vienna, Austria (N=150) and Timișoara, Romania (N=90). The replication revealed stable factor and item analytical results supporting the psychological substructure of urban QOL.
Keywords: Quality of life; wellbeing; environmental psychology; mixed methods; replication